Yield attributes of rice (Oryza sativa) as affected by integrated use of zinc oxide and zinc solubilizers - ASH, MOUMITA; YADAV, JANARDAN; YADAV, JAY SHANKAR (The Indian Journal of Agricultural Sciences, 2020)
Rice (Oryza sativa L.) is the staple food for more than three billion people around the world. Zinc (Zn) deficiency is mostly found in lowland rice due to submergence condition which affect the yield adversely. In view of limited information, a pot experiment was conducted at Department of Soil Science and Agricultural Chemistry, Institute of Agricultural Sciences, BHU, Varanasi, UP during kharif, 2018-19 to evaluate the response of rice to different levels of zinc oxide (ZnO) in combination with zinc solubilizing microbes. Zn deficient soil was collected from Agricultural Research Farm, IAS, BHU which were treated with three different doses of ZnO (0, 2.5 and 5 kg ha-1) along with three types of microbial inoculation, viz. no inoculation (M0), Enterobacter clocae strain ZnPSBJ-6 (M1) and zinc solubilizing fungi (M2). It was found that ZnPSBJ-6 has increased the grain yield by 57.2% and 101.4% while treated with Z1 (2.5 kg ha-1) and Z2 (5 kg ha-1) respectively compared to Z0. Whereas, in case of zinc solubilizing fungi, grain yield has increased by 96.4% and 127.1% in case of Z1 and Z2 respectively. On the other hand application of Z1 and Z2 have significantly increased the average straw yield by 28.9% and 36.5% respectively over the control.